Contribution of Home Based Psychosocial Issues On Students Academic Performance In Public Secondary Schools In Migori County, Kenya. - Okongo, Calvince; Odera, Florence Y.; Sichari, M. (Advances in Social Sciences Research Journal, 2020)
The home environment plays pivotal roles in determining children’s future. Every other parent strives to be a role model to be emulated by the children right from childhood to maturity level when these children can now stand strong to respond to the societal demands of life. However, when the home environment is not cordial to the children, this could lead to psychological, biological, mental and social dysfunction a reflection of cognitive disorientation especially for the students in secondary schools. The above situation would undoubtedly lead to a performance which does not measure to the threshold of the learning institutions in which the children have been admitted to pursue their studies .Students in high schools are in critical periods with myriads of psychological, social and academic issues which affect them most of which require personal and confidential psychotherapeutic interventions that the parents themselves could avert to ensure successful completion of secondary education. The key objective of the study was to establish the contribution of home based psychosocial issues on the students’ academic performance in public secondary schools in Migori County. The paper explores the extent to which parental attachment, socio economic status of parents and parental involvement which are all home based psychosocial factors contribute to the academic performance of both boys and girls .The study findings will challenge the care takers who in this case are the parents and guardians and teachers to understand the psychosocial turmoil students face as they struggle to make ends meet educationally. The findings of this study may assist the Government, NGOs, Principals and all the education stakeholders to understand and create more resources preferably trained personnel who could be knowledgeable in therapeutics skills to best manage students who might not have had the best home based care and attention.